2021
DOI: 10.1016/j.cub.2020.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Shapes Spontaneous Activity Patterns in the Developing Visual Cortex by Activating Somatostatin Interneurons

Abstract: Highlights d Oxytocin modulates spontaneous activity event patterns in the developing V1 d Oxytocin increases inhibition by activating somatostatin + interneurons d SST + neuron activity reduces event frequency and correlations, but not amplitude d In S1, oxytocin increases excitation and inhibition and does not modulate frequency

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…In cortical L2/3, SST interneuron synapses onto pyramidal cells emerge at the beginning of the second post-natal week (Guan et al, 2017), when oxytocin release also increases SST interneuron excitability and sparsifies neuronal activity (Maldonado et al, 2021). At this age, SST interneuron-mediated inhibition is strong and can be readily recorded in the somas of cortical pyramidal neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cortical L2/3, SST interneuron synapses onto pyramidal cells emerge at the beginning of the second post-natal week (Guan et al, 2017), when oxytocin release also increases SST interneuron excitability and sparsifies neuronal activity (Maldonado et al, 2021). At this age, SST interneuron-mediated inhibition is strong and can be readily recorded in the somas of cortical pyramidal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Image processing Two-photon As described previously (Maldonado et al, 2021), two-photon image processing drift and movement artifacts were removed from each recording using NoRMCorre (Pnevmatikakis and Giovannucci, 2017). Delta F stacks were made using the mean fluorescence per pixel as baseline.…”
Section: Quantification and Statistical Analysismentioning
confidence: 99%
“…This result may reflect actual changes in the number of SST+-neurons, or alternatively changes in SST expression and hence more reliable detection of SST-synthesizing neurons. Interestingly, OT modulates the activity of the SST+-neurons, increasing the excitability of SST interneurons (63) but no studies report an effect of OT on SST production.…”
Section: Discussionmentioning
confidence: 99%
“…We focused in S1 L2/3 pyramidal neurons for this study. Recent work showed that oxytocin affects spontaneous network events differentially in S1 and V1 (Maldonado et al, 2021 ). Given the complexity of the effects of oxytocin, studies on more cell types, more brain regions, and at more developmental stages, as well as more in-depth investigations of OXTR downstream signaling under these different conditions, are needed for a full understanding of its function.…”
Section: Discussionmentioning
confidence: 99%
“…Since we observed an increase in GABAergic input to L2/3 pyramidal neurons at P28, the increased OXTR expression likely enhanced the synaptic output of GABAergic neurons onto pyramidal neurons. A recent study indeed showed that oxytocin can enhance the excitability of SST neurons, thereby reducing the level of spontaneous activity (Maldonado et al, 2021).…”
Section: Effects Of Oxytocin On Synaptic Transmission At P28mentioning
confidence: 99%